2021
DOI: 10.1097/mao.0000000000003120
|View full text |Cite
|
Sign up to set email alerts
|

Improved Speech Intelligibility in Subjects With Stable Sensorineural Hearing Loss Following Intratympanic Dosing of FX-322 in a Phase 1b Study

Abstract: Objectives: There are no approved pharmacologic therapies for chronic sensorineural hearing loss (SNHL). The combination of CHIR99021+valproic acid (CV, FX-322) has been shown to regenerate mammalian cochlear hair cells ex vivo . The objectives were to characterize the cochlear pharmacokinetic profile of CV in guinea pigs, then measure FX-322 in human perilymph samples, and finally assess safety and audiometric effects of FX-322 in humans with chronic SNHL. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…This strongly suggests that the deafened mammalian cochlea retains regenerative potential, and hence therapeutic opportunities targeting the LGR5+ SCs could arise. A pioneering clinical trial has already shown that modulating the Wnt and Notch signaling pathway with a recently commercialized drug (FX322) in patients with sensorineural hearing loss improves speech recognition (both in quiet and in noise) 90 days after treatment ( McLean et al, 2021 ). This report, including only patients with noise-induced or idiopathic sudden SNHL, supports the hypothesis that Wnt-responsive SCs with regeneration potential are present in human, even after deafness.…”
Section: Discussionmentioning
confidence: 99%
“…This strongly suggests that the deafened mammalian cochlea retains regenerative potential, and hence therapeutic opportunities targeting the LGR5+ SCs could arise. A pioneering clinical trial has already shown that modulating the Wnt and Notch signaling pathway with a recently commercialized drug (FX322) in patients with sensorineural hearing loss improves speech recognition (both in quiet and in noise) 90 days after treatment ( McLean et al, 2021 ). This report, including only patients with noise-induced or idiopathic sudden SNHL, supports the hypothesis that Wnt-responsive SCs with regeneration potential are present in human, even after deafness.…”
Section: Discussionmentioning
confidence: 99%
“…In a Phase 1b trial, 23 subjects were randomized to treatment with FX-322 via intratympanic injection (n ¼ 15) or placebo (n ¼ 8). 45 There were no notable differences in treatment-related AEs between the FX-322and placebo-treated subjects. No drug-related systemic AEs occurred, and no clinically relevant changes were observed for clinical laboratory values, vital signs, ECG, otoscopy (with the exception of the single perforation), or tympanometry.…”
Section: Frequency Therapeutics: Combination Targets For Hair-cell Re...mentioning
confidence: 84%
“…When examining data from the WR in quiet test, McLean et al (2021) 45 showed 13 of 23 participants scored 90% or better (excellent performance) at baseline and due to ceiling effects, could not be assessed for efficacy. 46 The 10 remaining participants (6 FX-322 and 4 placebo) scored less than 90%, allowing for efficacy assessment using Thornton and Raffin's binomial distribution.…”
Section: Status Of Clinical Trials For Hair Cell Regenerationmentioning
confidence: 99%
“…In its first Phase 1/2 clinical trial, intratympanic FX‐322 showed variable improvement in word recognition scores in a quiet background for a small subset of subjects (5 of 15 patients) with mild to moderately severe hearing loss, and potential improvement in hearing thresholds at a single frequency (8 kHz) in a limited number of patients when administered as a single dose. 39 However, a follow‐on Phase 2a study, which evaluated single and multiple doses of FX‐322 in an attempt to overcome the short duration of cochlear exposure to the drug combination, 39 failed to show any improvement in similar audiologic endpoints. A concurrent open‐label single‐administration FX‐322 study in patients with mild to moderately severe hearing loss showed an improvement in word recognition scores in a subset of patients although a study in age‐related hearing loss showed no evidence of benefit.…”
Section: Hearing Loss Mechanisms and Therapeutic Strategiesmentioning
confidence: 99%